2022
DOI: 10.1007/s11482-022-10104-5
|View full text |Cite
|
Sign up to set email alerts
|

The Willingness to get Vaccinated Against SARS-CoV-2 Virus among Southeast Asian Countries: Does the Vaccine Brand Matter?

Abstract: The current study uses data surveyed with 2,500 respondents during August and September 2021 in Vietnam, Indonesia, the Philippines and Malaysia to examine the willingness to get vaccinated against SARS-CoV-2 virus with six COVID-19 vaccines. The willingness to get vaccinated varies according to the vaccine brands and selected influential factors. Particularly, the percentage of respondents who are willing to get vaccinated with Pfizer, Moderna and AstraZeneca dominates that of those who are willing to get vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 56 publications
1
11
0
1
Order By: Relevance
“…To estimate the minimum size of the sample, the mathematical formula suggested by Bujang et al (2018) and Duong and Antriyandarti (2022) was utilized:…”
Section: Participantsmentioning
confidence: 99%
“…To estimate the minimum size of the sample, the mathematical formula suggested by Bujang et al (2018) and Duong and Antriyandarti (2022) was utilized:…”
Section: Participantsmentioning
confidence: 99%
“…Vietnam has been identified as a suitable country for collecting data and applying the TPB to investigate how perceived benefits of COVID-19 vaccines can enhance the core components of the TPB and COVID-19 vaccination intention for the following reasons. Firstly, the effectiveness of the 5 K approach (Khẩu trang: mask wearing, Khử khuẩn: disinfection, Khoảng cách: social distancing, Không tụ tập đông người: No gatherings, and Khai báo y tế: health declaration) in controlling the spread of COVID-19 during the first three waves has been demonstrated in this country [ 12 , 38 ]. Secondly, during the time of the study, even though Vietnam was developing its own COVID-19 vaccine (Nanocovax), the majority of the Vietnamese population had only received one dose of a COVID-19 vaccine and they were waiting for international support in order to be vaccinated with their second and third doses of the vaccine [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, although some prior studies have investigated the willingness to receive COVID-19 vaccines and the acceptance of vaccination in Southeast Asian countries, the results were mixed and inconsistent, and more importantly, these studies did not explore individuals' COVID-19 vaccination intention in the light of the TPB. For example, Duong and Antriyandarti [ 38 ] surveyed 2500 respondents in four countries in Southeast Asia (Vietnam, Indonesia, the Philippines, and Malaysia) to examine the role of vaccine brand on individuals' willingness to be vaccinated against COVID-19 with six COVID-19 vaccines. This research revealed that a higher percentage of respondents express willingness to be vaccinated with Pfizer, Moderna, and AstraZeneca vaccines compared to Sinopharm, Janssen, and Sputnik-V vaccines while the influence of influential factors on the willingness to receive vaccination varies in terms of both magnitude and direction, and this variability was dependent on the specific vaccine brands.…”
Section: Introductionmentioning
confidence: 99%
“…As of 15 January 2023, there were more than 661 million total confirmed cases, with more than 6.7 million total deaths [ 4 , 5 ]. The COVID-19 pandemic has caused massive losses and socioeconomic panic worldwide [ 6 , 7 , 8 ]. In Vietnam, 11,525,711 infected people and 43,186 deaths were reported while the number of administered vaccine doses accounted for 265,518,865 [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…There have been numerous studies that have investigated the issue of COVID-19 vaccine intention and hesitancy in many countries, such as the USA [ 3 ], the United Kingdom, Canada [ 17 ], India [ 18 ] and others [ 19 ]. Noticeably, although some studies have been conducted to explore the issues of willingness to get vaccinated against COVID-19 and/or COVID-19 vaccine acceptance in Southeast Asian countries, including Vietnam [ 7 , 8 , 10 ], attention paid to explore the antecedents of vaccination intention and hesitancy is still scant.…”
Section: Introductionmentioning
confidence: 99%